Study on Track Frame Model of a Thai-Made Rice Combine Harvester - et. al., Khongdet Phasinam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A rice combine harvester has an important role in Thai rice production and has been popular in Thai farmer. Almost Thai-made rice combine harvester is too heavy and large in size. Because the track frame of Thai-made rice combine harvester is a main component that affects the harvester’s size and weight, the objectives of this research, therefore, were to investigate and improve the track frame strength using the finite element method (FEM). Similitude analysis was employed for determining the proper scale of experimental frame. The strength analysis using the loading test with experimental frame was used to verify the accuracy of the FEM. Two field-work conditions of the harvester’s header were selected namely horizontal position and maximum lift position. The FEM results showed that the maximum stresses of those conditions were 91.13 MPa and 91.69 MPa, respectively, while the maximum deflection 2.31 mm and 2.36 mm, respectively. The experimental results from the loading tests confirmed that the strength analysis of track frame using FEM had a high accuracy and could be applied in practical use. The improvement of the track frame model could increase the strength about 40% and reduce mass about 18%.